Extraction of sea ice area using AVHRR data of NOAA satellite - Tanaka, Shinya; Yamanouchi, Takashi; Kawaguchi, Sadao (1984)
P(論文) This paper presents a new method for extracting sea-ice information from the multi-spectral AVHRR images (visible, near-infrared and infrared images) of a TIROS-N/NOAA series satellite. The original image data are calibrated and corrected. The difference in albedo (reflectivity) between visible and near infrared images is obtained. Further, the difference in the brightness temperature between the 3.7 and 11μm infrared images is computed. The resulting images are formed from these two difference images and displayed on the image display using the false color technique. By applying this method to data observed during the daytime, the sea ice area and cloud area can be easily distinguished. departmental bulletin paper